2017
DOI: 10.1186/s13071-017-2498-5
|View full text |Cite
|
Sign up to set email alerts
|

On the complexity of measuring forests microclimate and interpreting its relevance in habitat ecology: the example of Ixodes ricinus ticks

Abstract: BackgroundEcological field research on the influence of meteorological parameters on a forest inhabiting species is confronted with the complex relations between measured data and the real conditions the species is exposed to. This study highlights this complexity for the example of Ixodes ricinus. This species lives mainly in forest habitats near the ground, but field research on impacts of meteorological conditions on population dynamics is often based on data from nearby official weather stations or occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Larvae are the most sensitive to high temperatures, which are usually associated with an increased mortality rate in I. ricinus , due to dehydration [ 58 ]. Boehnke et al [ 59 ] concluded that information gathered by using official weather data (i.e. meteoblue) is not always a good proxy of the actual microclimatic conditions the ticks experience.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae are the most sensitive to high temperatures, which are usually associated with an increased mortality rate in I. ricinus , due to dehydration [ 58 ]. Boehnke et al [ 59 ] concluded that information gathered by using official weather data (i.e. meteoblue) is not always a good proxy of the actual microclimatic conditions the ticks experience.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental predictor variables were standardized to a resolution of 30 arc seconds, which is equivalent to approximately 1 km 2 at the latitude of California. However, there is some mis-match in spatial scales, as ticks are also affected by microclimatic variables that vary on a much finer spatial scale ranging from a few centimeters to meters, for example soil temperature and humidity, which may vary markedly within an area [86,87].…”
Section: Discussionmentioning
confidence: 99%
“…As such, they emphasize the small scale at which local environmental factors may potentially affect the spatial distribution of pathogens. In a recent study, Boehnke et al 59 found that humidity can vary between open areas and forests as well as within different layers of a forest, directly affecting questing conditions for ticks. Indeed, the same is likely true for various other variables affecting tick questing and living conditions in different biotopes and structures [e.g., ground floor temperatures in shaded forests vs. open meadows (biotope type), different levels of canopy cover and wind shelter based on tree density (forest structure)] 60 .…”
Section: Discussionmentioning
confidence: 99%